The Influence of Cooperative Learning Model Type Think Talk Write (TTW) on Students Mathematical Communication Skills - Faridah, Siti Jaizah; Hikmah, Nurul; Azmi, Syahrul (Sigma&Mu: Journal of Mathematics, Statistics and Data Science, 2025)
This research was conducted to determine the effect of cooperative learning model type think talk write (TTW) on mathematical communication skills in students of SMPN 13 Mataram class VIII on statistics material. Quantitative approach with quasi experimental method was used in this research. The population in this study was all VIII grade students of SMPN 13 Mataram consisting of five classes, with a sample consisting of two classes, namely class VIII E as an experimental class using the cooperative learning model of think talk write (TTW) type and class VIII A as a control class using direct learning model. Data collection techniques used observation sheets, documentation, and tests. The results of data analysis showed that there was an average difference between the experimental and control classes. The t-test results obtained a t-count value of 2,939, and the t-table value obtained a value of 1,669, indicating that the t-count value was greater than the t-table. Thus, the Think Talk Write (TTW) cooperative learning model has a positive effect on students' mathematical communication skills. This research suggests the application of TTW model as an effective learning strategy to improve students' mathematical communication skills at junior high school level